Developing a Spatial Navigation Screening Tool Sensitive to the Preclinical Alzheimer Disease Continuum. (14th June 2019) - Allison, Samantha L; Rodebaugh, Thomas L; Johnston, Chiharu; Fagan, Anne M; Morris, John C; Head, Denise
Abstract: Objective: There remains a need for a non-invasive and cost-effective screening measure that could be administered prior to the provision of a lumbar puncture or positron emission tomography scan for the detection of preclinical Alzheimer disease (AD). Previous findings suggest that a hippocampally-based spatial navigation task may be effective for screening individuals for the preclinical AD continuum (i.e., low cerebrospinal fluid (CSF) Aβ42 ). Unfortunately, this task took 1.5–2 hours to administer, which would be time-prohibitive in a clinical setting. Therefore, the goal of this study was to compare psychometric properties of six spatial navigation-related tasks in order to take the next steps in developing a clinically appropriate screening measure. Methods: Psychometric properties (i.e., reliability, diagnostic accuracy, validity) of a modified version of the cognitive mapping task, two binding tasks, a visual perspective taking task, and self- and informant report versions of a questionnaire were examined in a sample of 91 clinically normal (CN) individuals. CSF Aβ42 and ptau181 were available for 30 individuals. Results: The learning phase of the cognitive mapping task and the self-report questionnaire were sensitive to identifying individuals in the preclinical AD continuum (93% and 87% sensitivity, 60% and 67% specificity, respectively). These two measures also demonstrated good test-retest stability (intraclass correlation coefficients = .719 and .838, respectively) and internal consistency (Cronbach's αs = .825 and .965, respectively). Conclusions: These findings suggest that a self-report questionnaire and aspects of a cognitive mapping task may be particularly appropriate for development as screening tools for identifying individuals in the preclinical AD continuum.